Fathering and Conjugality in Transnational Patchwork Families: the Angola/Portugal case - Grassi, Marzia (2014)
This paper explores long-distance fatherhood and the father-child relationships in transnational families between Angola and Portugal. Using evidence for the Portugal/Angola case in the second work package of the TCRAf-Eu project, we discuss the division of parental duties based on established gender roles (mother as caregiver and father as bread-winner) and how they are reconstructed in the long-distance context in which there are very few mothers living abroad: in our sample, the overwhelming majority of parents living in Portugal with children in Angola are fathers. Relational reconfigurations induced by absence are not always expected or controlled as changing roles within the family. We argue that besides the economic situation, conjugality and family gendered dynamics are crucial to an understanding of long-distance fatherhood practices and the long-distance father/child relationship